Representation, sophisticated voting, and the size of the gridlock region. (October 2017) - Kang, Myunghoon
We propose a formal model that investigates the institutional cause of the expansion of the gridlock region in a legislative body under supermajority rule. We show that the interaction between a legislative election and the supermajority rule in the legislative policy-making process causes an expansion of the size of the gridlock region under certain circumstances. More specifically, if the position of the status quo is neither too moderate nor too extreme, then certain voters will be incentivized to elect a more extreme representative than themselves, and this sophisticated voting results in the expansion of the size of the gridlock region. As a result, our model demonstrates that the expansion of the gridlock region is caused in part by sophisticated voting independent of the voters' ideological distribution.